THE USE OF PICTURE CARDS AS A COACHING MEDIA TO INCREASE THE LEARNING MOTIVATION OF SMK SAFINATUL HUDA STUDENTS IN HISTORY LEARNING - Tofan Priananda Adinata; Astri Ati Wahyuni; Dhalia Soetopo (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to (1) explain how the implementation of picture cards in coaching to increase the learning motivation of SMK Safinatul Huda students in history learning (2) determine the effectiveness of using picture cards as a coaching medium in increasing the learning motivation of SMK Safinatul Huda students in history learning. This study uses a qualitative method with a case study research type. Sampling was carried out using a purposive sampling technique (purposeful sampling). Data collection techniques used were observation, interviews, and document studies. The results of this study are the stages in implementing picture cards as a coaching medium, which include the planning stage, the implementation stage, and the evaluation stage. Student motivation has increased after participating in coaching using picture cards, which is evidenced by changes in student attitudes who initially felt less enthusiastic, unfocused, rarely did assignments, and easily bored and tired are now more enthusiastic, more focused during learning, and more diligent in doing assignments. This shows that the use of picture cards as a coaching medium is effective in increasing the learning motivation of SMK Safinatul Huda students in history learning.